2010
DOI: 10.1105/tpc.110.073957
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation of Transcriptional Auxin Response Networks inArabidopsis thaliana     

Abstract: Natural variation has been observed for various traits in Arabidopsis thaliana. Here, we investigated natural variation in the context of physiological and transcriptional responses to the phytohormone auxin, a key regulator of plant development. A survey of the general extent of natural variation to auxin stimuli revealed significant physiological variation among 20 genetically diverse natural accessions. Moreover, we observed dramatic variation on the global transcriptome level after induction of auxin respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 59 publications
6
78
0
1
Order By: Relevance
“…To further elucidate the genetic architecture of the growing leaf's responses to mild drought, the natural variation in transcriptome responses was investigated. Measuring transcriptional differences between Arabidopsis accessions has indicated a substantial variation in gene expression in different conditions Delker et al, 2010;Des Marais et al, 2012;Clauw et al, 2015). Also in our specific experimental setup, considerable expression variation was observed between the different accessions.…”
Section: Genetic Architecture Of Mild Drought Responses In Leavesmentioning
confidence: 84%
See 2 more Smart Citations
“…To further elucidate the genetic architecture of the growing leaf's responses to mild drought, the natural variation in transcriptome responses was investigated. Measuring transcriptional differences between Arabidopsis accessions has indicated a substantial variation in gene expression in different conditions Delker et al, 2010;Des Marais et al, 2012;Clauw et al, 2015). Also in our specific experimental setup, considerable expression variation was observed between the different accessions.…”
Section: Genetic Architecture Of Mild Drought Responses In Leavesmentioning
confidence: 84%
“…For some traits, the expression variation of the regulatory network can be more important than polymorphisms that affect gene function. This was shown for the regulatory network of auxin responses (Delker et al, 2010). Adaptation by gene expression variation may be especially important in quantitative traits for which characteristics of the function, such as the rate, size, or duration, differ.…”
Section: Genetic Architecture Of Mild Drought Responses In Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted, however, that our Winter accessions were not subjected to cold treatment; therefore, some observed differences between Col and the Winter accessions may arise from the latter being in an extended vegetative phase. That transcriptional stress response in Col is not a strong predictor of the response of other accessions has been noted previously with respect to cold stress response and exogenous treatment with auxin (Delker et al, 2010) and salicylic acid (van Leeuwen et al, 2007).…”
Section: Comparison To Past Studies: How Representative Is the Col Gementioning
confidence: 93%
“…Auxins are synthesized specifically in maternal sporophytic tissue during megasporogenesis, and mutants affected in auxin biosynthesis are defective in the establishment of the gametophytic phase (Stepanova et al, 2008;Pagnussat et al, 2009;Bencivenga et al, 2011). AGP18 expression is induced by natural auxin indole-3-acetic acid in diverse Arabidopsis ecotypes (Delker et al, 2010) and repressed by ABA (Zhang et al, 2011a), consistent with the observed overexpression of AGP18 mRNA in the ABA signaling double mutant agb1 gpa1, which is defective in proteins GTP BINDING PROTEIN BETA1 (AGB1) and G PROTEIN ALPHA SUBUNIT1 (GPA1; Hruz et al, 2008;Pandey et al, 2010). Our results extend these findings by showing that hormone-related response elements are necessary for proper sporophytic expression of AGP18 during megasporogenesis.…”
Section: Discussionmentioning
confidence: 99%